Unveiling the drivers of islamic bank profitability : fundamental and macroeconomic factors in Asia - Mar'atus Sholihah; Guntur Kusuma Wardana (Jurnal Akademi Akuntansi)
Purpose: This research aims to analyze the influence of fundamental and macroeconomic factors on the profitability of Islamic banking in Asia during 2019–2023.